PEMBENTUKAN PERILAKU ANTI KORUPSI TERHADAP PEJABAT DI ACEH MELALUI REGIULITAS - Benazir Benazir (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2022)
Religiosity factor is not a factor that determines corrupt behavior. corrupt and non-corrupt behavior cannot be explained by the level of religiosity or piety. However, the more religious a person is, the more they value anticorruption. The results obtained from the Monitoring Center For Prevention (MCP) show an increase in the prevention of corruption in Aceh. In 2018 the aggregate value of Aceh's MCP was at 43 percent, then in 2019 it rose to 46 percent, in 2020 Aceh's MCP aggregate value was at 50 percent, in 2021 Aceh's MCP aggregate value improved, reaching 72.2 percent. This means that with the implementation of the MCP program it can be seen that there are continuing improvements in Aceh. The data shows that the level of corruption in Aceh province in 2021 will decrease. This indicates that the people of Aceh generally have a good level of regularity. Officials in Aceh province have religious knowledge, religious beliefs, practice of religious rituals, religious experience, behavior (morality) meaning religion, and good religious social attitudes.